The Effect of Autogenic Relaxation on Blood Pressure in Hypertensive Patients - Anita Shinta Kusuma; Evin Kristiani (Jurnal Kesehatan, 2021)
Hypertension case is increasing from year to years. Based on World Health Organization (WHO) data in 2015 showed around 1.13 billion people in the world have hypertension, meaning 1 in 3 people in the world are diagnosed with hypertension. Hypertension is often referred to as a "silent killer", because many people with hypertension do not feel any signs and symptoms, and then after some years they experience complications. One way to control blood pressure in hypertensive patients is to use non-pharmacological therapy interventions. One of them is to use autogenic relaxation methods. Autogenic relaxation is a method that comes from self and body awareness by controlling muscle and liver tension for the improvement of high blood pressure caused mainly by stress. Autogenic relaxation will help the body to carry commands through autosuggestion to relax so that it can control blood pressure, heart rate and body temperature. The purpose of this study is to describe the influence of autogenic relaxation to decrease the blood pressure of hypertensive patients. This study uses the literature review method. The result of this study shows that several literatures on autogenic relaxation proved that this intervention is very effective for hypertensive patients and can be used as a complementary intervention in hypertensive patients.